Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

Solve x: 3x-7 = 5x+13
Solve x: 7-3x = 5x+13


Sagot :

first you need to combine like terms
7-3x= 5x+13
step 1 add 3x
7=8x+13
step 2 subteact 13
-6=8x
step 3 divide both sides by two
x=-3/4
heyDB
1.
Since 5x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 5x from both sides.
3x−7−5x=13

Add 3x and −5x to get −2x.
−2x−7=13

Move -7 to the right hand side of the equation.
−2x=7+13

Add 7 and 13 to get 20.
−2x=20

Divide each term in the equation by −2.

x=−10

2.
Since 5x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 5x from both sides.
7−3x−5x=13

Add −3x and −5x to get −8x.
7−8x=13

Move 7 to the right hand side of the equation.
−8x=−7+13

Add −7 and 13 to get 6.
−8x=6

Divide each term in the equation by −8.

x=−3/4
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.